Respiratory Presentation of Pediatric Patients in the 2014 Enterovirus D68 Outbreak. (16th August 2016) - Martin, Georgina; Li, Rachel; Cook, Victoria E.; Carwana, Matthew; Tilley, Peter; Sauve, Laura; Tang, Patrick; Kapur, Akshat; Yang, Connie L.
Abstract : Background . In the fall of 2014, a North American outbreak of enterovirus D68 resulted in a significant number of pediatric hospital admissions for respiratory illness throughout North America. This study characterized the clinical presentation and risk factors for a severe clinical course in children admitted to British Columbia Children's Hospital during the 2014 outbreak. Methods . Retrospective chart review of patients with confirmed EV-D68 infection admitted to BCCH with respiratory symptoms in the fall of 2014. Past medical history, clinical presentation, management, and course in hospital was collected and analyzed using descriptive statistics. Comparison was made between those that did and did not require ICU admission to identify risk factors. Results . Thirty-four patients were included (median age 7.5 years). Fifty-three percent of children had a prior history of wheeze, 32% had other preexisting medical comorbidities, and 15% were previously healthy. Ten children (29%) were admitted to the pediatric intensive care unit. The presence of complex medical conditions (excluding wheezing) (P = 0.03 ) and copathogens was associated with PICU admission (P = 0.02 ). Conclusions . EV-D68 infection resulted in severe, prolonged presentations of asthma-like illness in the hospitalized pediatric population. Patients with a prior history of wheeze and preexisting medical comorbidities appear to be most severely affected, but the virus can also cause wheezing in previously well children.